The greatest lie of all - Cantor, Jillian (Park Row Books, 2024)
"Fledgling actress Amelia Grant is at rock bottom when offered the opportunity of a lifetime: to star in a biopic about the world-renowned romance author Gloria Diamond, who used her own tragic love story as inspiration for her bestselling books. To prepare for the role, she'll spend a week with Gloria at her secluded Washington estate. It's a chance to get out of LA, away from her cheating ex-boyfriend, and to make her recently deceased mother proud. Amelia's excitement is short-lived, however, once she actually meets Gloria, who is cold, verging on rude and mostly unavailable. If not for Gloria's frustratingly handsome son Will, the visit might be a complete waste of her time. But when Amelia stumbles upon a secret from Gloria's past, she realizes Gloria's life story is more fiction than fact. And as the movie's filming date draws nearer, Amelia must decide how much she's willing to sacrifice to uncover the truth"--